Daily Report Process and Production - Istianto Budhi Rahardja; Srinita Panjaitan; Yudi Dermawan (Politeknik Kelapa Sawit Citra Widya Edukasi, 2021)
The daily report is a form of data display as evidence of the implementation of daily work. The daily process report is a report that contains the daily operations of the factory, and the daily production report is a report that contains data on the daily production results of the factory. The purpose of this study was to find out the meaning of the daily process report and production daily report, to find out the parts of the daily production report, to find out the contents of the daily process report and to know how to fill in the daily production report. The data needed is daily laboratory data, weighbridge station and sorting, production process department and data on CPO and Kernel sounding results. The results show that the daily production report contains various information related to the production achievements of a palm oil mill.